Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1021/cm801680c
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Structural Properties of Ce−Zr Mixed Oxide Nanotubes

Abstract: In this work, ZrO2−CeO2 mixed oxide nanotubes with 50, 70, and 90 mol % CeO2 were synthesized following a very simple, high yield procedure, and their properties were characterized by synchrotron radiation XRD and by high resolution electron microscopy. The 50, 70, and 90 mol % CeO2 nanotubes exhibited the tetragonal phase (t′-form and t′′-form, P42/nmc space group) or the cubic phase (Fm3m space group). The nanotube walls were composed of nanoparticles with an average crystallite size ranging from 4.7 to 7.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…In this sense, we are currently working on the use of Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3 nanotubes and other cobaltites as IT-SOFC cathode, and on their use in anode materials and catalysts [25].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, we are currently working on the use of Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3 nanotubes and other cobaltites as IT-SOFC cathode, and on their use in anode materials and catalysts [25].…”
Section: Discussionmentioning
confidence: 99%
“…The selected area electron diffraction (SAED) pattern (Fig. 2a) indicates that the sample consisted of very small crystallites, and was indexed to the cubic fluorite phase of ceria based on the interplanar spacing of 0.31 nm [15,16]. HRTEM images further indicated that these particles preferentially exposed the {1 1 1} crystal plane of ceria.…”
Section: Ethanol Oxidationmentioning
confidence: 99%
“…As a practical approach for minimizing Ce loading on nanomaterials, CeO 2 -ZrO 2 nanocomposites can be used as a substitute because of their chemical, mechanical, and thermal stability. Also, some of CeO 2 -ZrO 2 mixed oxides have been reported to show better catalytic performance compared to CeO 2 itself [9]. In order to achieve high performance, controlling the composition, topology, and morphology of CeO 2 -ZrO 2 composites at the nano level is very important.…”
Section: Introductionmentioning
confidence: 99%